Students’ Perception of Distance Learning: A Case Study on the Students of Politeknik Negeri Jember - Vigo Dewangga; Renata Kenanga Rinda (Penerbit STKIP PGRI Bangkalan, 2021)
Nowadays, the Corona virus outbreak has made a huge change in education, especially for the teaching-learning process. Lecturers should do teaching from home and the students should do learning from home. Both the students and the lecturer just stay at home, they could not go to campus and office to do offline teaching- learning process to keep away from the spread of corona virus. Whether one likes it or not, all the lecturers should create an fascinating and innovative distance learning class. Some online learning platforms have been available on the internet that can help teacher in delivering their materials, for examples Google Classroom, Edmodo, Kahoot, and many others. In addition, there are some video conference applications for doing video call on the distance learning, for example Zoom, skype, Cisco WebEx, Google Meet and many others. As a lecturer, we could choose which online learning platforms we are going to apply in our distance learning class. This study focuses on students’ perceptions of distance learning quality during the outbreak of covid 19. The research involved 70 participants consist of students of the cultivation of plantation crops Department in the fourth semester in the Agricultural Production, Politeknik Negeri Jember. The data collection techniques used in this research consisted of questionnaire, and interviews and were analyzed using the qualitative methods approach. The results of the study revealed that the majority of participants considered exciting and enthusisastic the distance learning in Applied English course.